1999
DOI: 10.1093/ije/28.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and cardiovascular risk factors in the Czech Republic

Abstract: Socioeconomic differences in cardiovascular risk factors in Czech Republic in 1992 had the same direction and similar magnitude as in Western Europe, and were strongly related to education rather than material conditions. Materialist explanations for the social differences seem unlikely in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 24 publications
5
32
0
4
Order By: Relevance
“…There is an association between the prevalence of cardiovascular risk factors and the level of education, 6 which was also confirmed in our population. 7 Our study found a high population mean of BMI and increasing BMI and prevalence of obesity in the male population. The relationship between hypertension and obesity is well established: BP increases with increasing body weight, and the incidence of hypertension among the obese approaches 50%.…”
Section: Discussionsupporting
confidence: 49%
“…There is an association between the prevalence of cardiovascular risk factors and the level of education, 6 which was also confirmed in our population. 7 Our study found a high population mean of BMI and increasing BMI and prevalence of obesity in the male population. The relationship between hypertension and obesity is well established: BP increases with increasing body weight, and the incidence of hypertension among the obese approaches 50%.…”
Section: Discussionsupporting
confidence: 49%
“…The details have been described elsewhere (Bobak et al, 1999); briefly, 1141 men and 1212 women aged 25-64 y, randomly selected from the population registers of six Czech districts, have been invited to participate in the study. Participants (response rate 76%) completed a questionnaire, gave a blood sample and underwent a short examination in a clinic.…”
Section: Methodsmentioning
confidence: 99%
“…The relation between education and health is wellestablished; persons who are better educated live longer and suffer less morbidity during their lifetimes (Hemingway et al, 2000;Bobak et al, 1999;Lynch et al, 1995). However, the relation between education and use and misuse of substances is less consistent.…”
Section: Introductionmentioning
confidence: 99%